Eco-Friendly Synthesis and Characterization of Ni-Si Nanoparticles Mixed Oxides as Catalyst for (Journal of Sciences, Islamic Republic of Iran)
The nanoparticles of Ni–Si mixed oxides were prepared by co-precipitation method using nickel nitrate; Ni(NO3)2 6H2O and tetraethylorthosilicate (TEOS). The products were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), and hydrogen temperature program reduction (H2-TPR). The results revealed that Ni–Si mixed oxides particles were obtained with average particle size 1-2 nm. The Ni-Si nanoparticles mixed oxides successfully catalyzed the partial oxidation of methane (POM) to hydrogen and carbon monoxide (Syn gas) using a fixed-bed reactor with about 92% activity and high selectivity. No coke formation and deactivation of catalyst were observed during the course of reaction. Particularly significant is the similar reactivity of this catalyst with that of Ni-Ce-Zr mixed oxides.